The feeding behaviour of Amyotrophic Lateral Sclerosis mouse models is modulated by the Ca2+‐activated KCa3.1 channels. (5th October 2021) - Cocozza, Germana; Garofalo, Stefano; Morotti, Marta; Chece, Giuseppina; Grimaldi, Alfonso; Lecce, Mario; Scavizzi, Ferdinando; Menghini, Rossella; Casagrande, Viviana; Federici, Massimo; Raspa, Marcello; Wulff, Heike; et al.
Abstract : Background and Purpose: Amyotrophic lateral sclerosis (ALS) patients exhibit dysfunctional energy metabolism and weight loss, which is negatively correlated with survival, together with neuroinflammation. However, the possible contribution of neuroinflammation to deregulations of feeding behaviour in ALS has not been studied in detail. We here investigated if microglial KCa 3.1 is linked to hypothalamic neuroinflammation and affects feeding behaviours in ALS mouse models. Experimental Approach: hSOD1 G93A and TDP43 A315T mice were treated daily with 120 mg·kg −1 of TRAM‐34 or vehicle by intraperitoneal injection from the presymptomatic until the disease onset phase. Body weight and food intake were measured weekly. The later by weighing food provided minus that left in the cage. RT‐PCR and immunofluorescence analysis were used to characterize microglia phenotype and the main populations of melanocortin neurons in the hypothalamus of hSOD1 G93A and age‐matched non‐tg mice. The cannabinoid–opioid interactions in feeding behaviour of hSOD1 G93A mice were studied using an inverse agonist and an antagonist of the cannabinoid receptor CB1 (rimonabant) and μ‐opioid receptors (naloxone), respectively. Key Results: We found that treatment of hSOD1 G93A mice with the KCa 3.1 inhibitor TRAM‐34 (i), attenuates the pro‐inflammatory phenotype of hypothalamic microglia, (ii) increases food intake and promotes weight gain, (iii) increases the number of healthy pro‐opiomelanocortin (POMC) neurons and (iv), changes the expression of cannabinoid receptors involved in energy homeostasis. Conclusion and Implications: Using ALS mouse models, we describe defects in the hypothalamic melanocortin system that affect appetite control. These results reveal a new regulatory role for KCa 3.1 to counteract weight loss in ALS.